Early-onset leukoencephalopathy due to a homozygous missense mutation in the DARS2 gene. Issue 5 (October 2015) - Köhler, Cornelia; Heyer, Christoph; Hoffjan, Sabine; Stemmler, Susanne; Lücke, Thomas; Thiels, Charlotte; Kohlschütter, Alfried; Löbel, Ulrike; Horvath, Rita; Kleinle, Stephanie; Benet-Pages, Anna; Abicht, Angela
Abstract: Mutations in the DARS2 gene are known to cause leukoencephalopathy with brainstem and spinal cord involvement and lactate elevation (LBSL), a rare autosomal recessive neurological disorder. It was originally described as juvenile-onset slowly progressive ataxia and spasticity, but recent reports suggest a broader clinical spectrum. Most patients were found to carry compound heterozygous DARS2 mutations, and only very few patients with homozygous mutations have been described so far. We present here an 8-month-old boy carrying a homozygous missense mutation in DARS2 who clinically showed severe neurological deterioration after a respiratory tract infection, followed by an almost complete remission of symptoms. This report further extends the knowledge about the clinical and molecular genetic spectrum of LBSL. Highlights: We present a boy with leukoencephalopathy due to a homozygous DARS2 mutation. Homozygous mutations in the DARS2 gene are rarely described. The favourable outcome of the young boy is unusual for DARS2 mutations. The MRI pattern is not typical for the DARS2 associated leukoencephalopathy (LBSL).